Beyond Facial Beauty. The Aesthetics of Yoruba Culture in Tiro Eye-Liner - Ojo, Abayomi C.; Boluwatife, Ajibola Deborah (Journal of Gender and Power, 2025)
There are many distinctive features of Yoruba culture and tradition that distinguish the Yoruba people of Southwestern Nigeria from other ethnic groups. Cultural practices and their aesthetic values shape the identity of African societies, often characterized by animistic beliefs. The veneration of ancestors and other presumed supernatural beings has given rise to the organization of festivals and rituals, which are reflected in various forms of physical adornment among African peoples. This paper examines the application of tiro (eye-liner) as a cultural practice that embodies multiple symbolic meanings. Despite the traditional values attached to tiro, this cosmetic practice is increasingly threatened by modern beauty products. Today, tiro has undergone a process of modernization that has weakened its connection to cultural and traditional practices associated with ancestral worship. There is limited academic research on tiro as a traditional cosmetic imbued with cultural significance. This paper identifies and examines the relationship between tiro and the worship of deities and other mystical beings in Yoruba performances. The study is based on a close examination of historical documents related to the subject. As part of a broader exploration of the belief system and cultural values of the Yoruba people, video interviews and personal presentations are also analyzed to highlight the syncretism between tiro and cultural practices. Within the cultural context, many activities and practices possess symbolic meanings that make them more metaphysical than physical. Tiro is a cosmetic used primarily to enhance facial beauty, especially among women. However, it also plays a significant role in Yoruba culture, particularly in festivals and ritual practices. It serves as a symbolic link between the living and their ancestors, as some worshippers apply it during ritual performances and sacrificial ceremonies dedicated to deities. Beyond its cosmetic function, tiro reflects the aesthetic values and spiritual dimensions of Yoruba tradition.